Can the Air Force and Airlines Collaborate for Mutual Benefit? An Exploration of Pilot and Maintenance Workforce Options - Rosello, Anthony D. (RAND Corporation, 2016)
This report encapsulates the analysis and results of the Air Force-Airline Industry Collaboration project, which investigated the viability of options for the Air Force and commercial airlines to collaborate on issues related to their pilot and maintenance workforces by evaluating benefits, costs, and feasibility from the perspectives of both sides.